Protein-Protein Interactions at the Adrenergic Receptors - Cotecchia, Susanna (Bentham Science Publishers, 2012)
The adrenergic receptors are among the best characterized G protein-coupled receptors (GPCRs) and knowledge on this receptor family has provided several important paradigms about GPCR function and regulation. One of the most recent paradigms initially supported by studies on adrenergic receptors is that both βarrestins and G protein-coupled receptors themselves can act as scaffolds binding a variety of proteins and this can result in growing complexity of the receptor-mediated cellular effects. In this review we will briefly summarize the main features of βarrestin binding to the adrenergic receptor subtypes and we will review more in detail the main proteins found to selectively interact with distinct AR subtype. At the end, we will review the main findings on oligomerization of the AR subtypes.